2016
DOI: 10.1515/ffp-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

First report of Geosmithia langdonii and Geosmithia spp. isolated from a decaying elm (Ulmus minor) in Geneva, Switzerland

Abstract: The mortality of a young elm Ulmus minor in 2014 in Geneva prompted a search for the microorganisms potentially involved. Symptoms included foliar chlorosis and wilting followed by defoliation of branches. Wood symptoms included a brown streaking of sap wood and brown stains in trunk and branches. The comparison of the resulting ITS rDNA sequences to the NCBI Nucleotide database allowed to identify 10 different organisms. The genus Geosmithia represented 48% of the isolates belonging to three species: Geosmith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…A similar effect is well known in Trichoderma fungi that not only protect plants directly by killing other fungi and nematodes but also induce resistance against plant pathogens [ 51 ]. Based on these results, Geosmithia is not a pathogen on elm, in contrast with the observation by Hänzi et al [ 60 ]. In no case, we were able to re-isolate Geosmithia from artificially infected elms, nor was it reported among the endophytic cohort of saprotrophs of elm trees [ 61 ].…”
Section: Discussioncontrasting
confidence: 57%
“…A similar effect is well known in Trichoderma fungi that not only protect plants directly by killing other fungi and nematodes but also induce resistance against plant pathogens [ 51 ]. Based on these results, Geosmithia is not a pathogen on elm, in contrast with the observation by Hänzi et al [ 60 ]. In no case, we were able to re-isolate Geosmithia from artificially infected elms, nor was it reported among the endophytic cohort of saprotrophs of elm trees [ 61 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Concurringly, it was identified as the dominant fungi in a U. minor tree with extensive dieback symptoms in the absence of DED pathogens (Hänzi et al, 2016). Certain Geosmithia fungi could therefore act as opportunistic or latent pathogens in elms, as previously reported by Hänzi et al (2016). The presence of this genus in the healthy tree (RIV5) suggests that it is able to live as an endophyte in latent pathogenicity.…”
Section: Phenotypic Vitality and Wood Mycobiomementioning
confidence: 67%
“…was extremely abundant in the declining tree RIV2. Concurringly, it was identified as the dominant fungi in a U. minor tree with extensive dieback symptoms in the absence of DED pathogens (Hänzi et al, 2016). Certain Geosmithia fungi could therefore act as opportunistic or latent pathogens in elms, as previously reported by Hänzi et al (2016).…”
Section: Phenotypic Vitality and Wood Mycobiomementioning
confidence: 68%
“…langdonii and other Geosmithia spp. from Ulmus minor afflicted with Dutch elm disease in Switzerland, although their role was not described (Hänzi et al ., 2016). Furthermore, G .…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported isolation of G. langdonii and other Geosmithia spp. from Ulmus minor afflicted with Dutch elm disease in Switzerland, although their role was not described (Hänzi et al, 2016). Furthermore, G. langdonii and G. levendula produce bioactive compounds with antimicrobial and antileishmanial activities (Stodulkova et al, 2010;Malaka et al, 2013).…”
Section: Introductionmentioning
confidence: 99%